457 NUTRITION, SARCOPENIA AND FRAILTY. (14th June 2021) - Du, W
Abstract:  : Many older people admitted to hospital are malnourished/at risk of malnourishment (30%), have swallowing problems (55%), are frail (25%), have sarcopenia (50%) or a combination of these. On admission to hospital frail older people are at significant risk of worsening nutritional status and prolonged hospital stay. Nutritional status should be identified, documented, food intake monitored and where appropriate they should be referred to the dietitian. The question remains, do staff recognise that frail older people may not eat their food increasing their risk of poor nutrition and outcome. Methods: Older people admitted to a 'Frailty' Ward were directly observed during lunchtime by WD. The Minimal Eating Observation Form –Version II (MEOF-II) was used to document how much they ate. Frailty status (CFS), presence of Sarcopenia (Sarc-F) and whether a referral to dietetics or speech and language therapy (SLT) was completed. Results: 39 patients were observed. Mean age was 82.38 years; median CFS 6 (3–8); median Sarc-F 4(0–9). Median MEOF II was 0 (0–5). Two patients were referred to dietetics and 4 to SLT. 7/40 (17, 5%) were at high risk for undernutrition, a further 8/40(20%) were at moderate risk. 82% were severely frail, the remaining were mildly frail. 94% (16/17) exhibited sarcopenia. There was significant correlation between MEOF II and CFS (r = 0.4887, p = 0.00162); MEOFII and Sarc-F (r = 0.4395, p = 0.00512). There was correlation between CFS and Sarc-F (r = 0.80296, p < 0.00001). Only one (6%) was referred to the dietitian. Conclusion: Frail older adults are often undernourished on admission to hospital. Nutritional intake is often poor with acute illness. Screening, observation and monitoring of nutritional intake should highlight concerns and needs for intervention. These study high lights that a significant number of older people are frail, fail to complete meals, are at significant risk of under nutrition, yet proactive intervention does not occur.